Integration of Data Governance and Development of Business Intelligence Dashboard for Decision-Making in Regional Water Utility - Cindy Sinaga; Gohan Sihite (Governance IT Adoption and Technology Advance, 2026)
Public service organizations need effective data management in order to deliver better services and improve decision making. This study analyzes the implementation of Data Governance and Business Intelligence at Perumda Air Minum. Prior to the conduct of this study, customer complaint data was captured manually, and the formats of those inputs were disparate. This resulted in unreliable information. The study took a qualitative descriptive approach using observation, interviews and document analysis. Data Governance was formalised by cleansing, validating, and managing data quality. Google Spreadsheet was used as a staging layer where customer complaint information was ingested through an Application Programming Interface (API) connection. The data was then This data was then visualised with a Business Intelligence dashboard using Looker Studio. Insights were offered for complaint trends, category distributions, branch-level complaint analysis, and operational monitoring tables on the dashboard. The study finds that Data Governance enhanced data consistency, completeness and reliability of reports. The Business Intelligence dashboard helped with operational monitoring and decision making as well. Further, the combination of Data Governance and Business Intelligence enhanced reporting efficiency and organizational transparency.